2021
DOI: 10.1016/j.jbc.2021.100583
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Notch3 in osteoblasts/osteocytes causes compartment-specific changes in bone remodeling

Abstract: Notch receptors maintain skeletal homeostasis. NOTCH1 and 2 have been studied for their effects on bone remodeling. Although NOTCH3 plays a significant role in vascular physiology, knowledge about its function in other cellular environments, including bone, is limited. The present study was conducted to establish the function of NOTCH3 in skeletal cells using models of Notch3 misexpression. Microcomputed tomography demonstrated that Notch3 null mice did not have ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 81 publications
0
12
0
Order By: Relevance
“…Previous studies have shown that LPS (Dong et al, 2018b), IL-6,TGF-b, parathyroid hormone -related protein (PTHrP) (Yasuda, 2021), IGF-1 (Huang et al, 2018;Yasuda, 2021), and other inflammatory factors facilitate RANKL expression. During osteoclast differentiation, activated T nuclear factor (NFATc1) is a major transcription factor, which can be activated by RANKL binding to its receptor RANK to promote osteoclast differentiation (Canalis et al, 2021). Additionally, TNF receptorassociated factor 6 (TRAF6) in osteoclast precursors is necessary to mediate RANKL-induced NF-kB activation and osteoclast formation and activation.…”
Section: Ranklmentioning
confidence: 99%
“…Previous studies have shown that LPS (Dong et al, 2018b), IL-6,TGF-b, parathyroid hormone -related protein (PTHrP) (Yasuda, 2021), IGF-1 (Huang et al, 2018;Yasuda, 2021), and other inflammatory factors facilitate RANKL expression. During osteoclast differentiation, activated T nuclear factor (NFATc1) is a major transcription factor, which can be activated by RANKL binding to its receptor RANK to promote osteoclast differentiation (Canalis et al, 2021). Additionally, TNF receptorassociated factor 6 (TRAF6) in osteoclast precursors is necessary to mediate RANKL-induced NF-kB activation and osteoclast formation and activation.…”
Section: Ranklmentioning
confidence: 99%
“…The effect of Notch3 ASOs was tested in cells of the osteoblast lineage since previous work demonstrated that Notch3 is preferentially expressed in these cells and is not expressed in cells of the myeloid lineage [ 16 , 51 , 52 ]. Mouse Notch3 ASOs added to the culture medium of osteoblast-enriched cells from C57BL/6 mice at 20 μM decreased Notch3 mRNA by ~60 to 80% 72 h after ASO addition without microscopic evidence of cellular toxicity or substantial changes in cell replication ( Fig 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Notch3 ASOs decreased Notch3 mRNA in osteoblasts and bone marrow stromal cells from wild type and Notch3 em1Ecan mice and Notch3 6691TAAGTA mutant mRNA in Notch3 em1Ecan cells for periods of up to 21 days ( Fig 2 ). The inhibitory effect of Notch3 ASOs was also observed in osteocyte-enriched cells, a cellular environment that preferentially expresses Notch3 [ 51 , 52 ]. In this culture system, Notch3 ASOs inhibited Notch3 expression in wild type and Notch3 em1Ecan mice and also suppressed the expression of Notch3 6691-TAATGA mRNA in Notch3 em1Ecan mutant cells, although this effect did not reach statistical significance ( Fig 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations